Should We Exclude Live Donor Liver Transplantation for Liver Transplant Recipients Requiring Mechanical Ventilation and Intensive Care Unit Care? - Goldaracena, Nicolas (Transplant Direct, 2015)
Patients with acute and chronic liver disease often require admission to intensive care unit (ICU) and mechanical ventilation support before liver transplantation (LT). Rapid disease progression and high mortality on LT waiting lists makes live donor LT (LDLT) an attractive option for this patient population. METHODS: During 2000 to 2011, all ICU-bound and mechanically ventilated patients receiving an LDLT (n = 7) were compared to patients receiving a deceased donor LT (DDLT) (n = 38). RESULTS: Both groups were comparable regarding length of pretransplant ICU stay (DDLT: 2 [1-31] days vs LDLT: 2 [1-8] days; P = 0.2), days under mechanical ventilation (DDLT: 2 [1-31] days vs LDLT: 2 [1-5] days; P = 0.2), pretransplant dialysis (DDLT: 45% vs LDLT: 43%; P = 1) and model for end-stage liver disease score (DDLT: 33 ± 8 vs LDLT: 33 ± 10; P = 0.911). Live donors median evaluation time was 24 hours (18-561 hours). As expected, median time on waiting list was significantly lower in the LDLT group (DDLT: 13 [0-1704] days vs LDLT: 10 [1-33] days; P = 0.008). Incidence of postoperative complications was numerically, albeit not significantly higher in the DDLT versus LDLT (68% vs 29%; P = 0.08). No difference was detected between LDLT and DDLT patients regarding 1-year (DDLT: 76% vs LDLT: 85%), 3-year (DDLT: 68% vs LDLT: 85%), and 5-year (DDLT: 68% vs LDLT: 85%) graft and patient survivals (P = 0.41). No severe donor complication occurred after live donation. CONCLUSIONS: The LDLT may provide a faster access to transplantation and therefore, offers an alternative treatment option for critically ill patients requiring ICU care and mechanical ventilation support at the time of transplantation.